Psychosocial Risk and its Association with Outcomes in Continuous-Flow Left Ventricular Assist Device Patients - DeFilippis, Ersilia M. (Circ Heart Fail, 2020)
BACKGROUND: Advanced heart failure therapies such as left ventricular assist device (LVAD) implantation require intricate follow-up and complex care. We sought to explore the burden of psychosocial risk factors among LVAD patients and their impact on post-implant outcomes using Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS). METHODS: Adult patients in INTERMACS requiring durable LVAD between 2008–2017 were included. Individuals were determined to have psychosocial risk if they had one of the following: 1) limited social support; 2) limited cognition; 3) substance abuse (alcohol and/or drug); 4) severe psychiatric disease (including major depression and/or other major psychiatric diagnosis), and 5) repeated non-compliance. Univariate and multivariate Cox proportional hazard regression models were used to analyze predictors of survival and complications. RESULTS: 15,403 continuous-flow LVAD recipients were included. 3163 (20.5%) had one or more psychosocial risk factors. The most prevalent psychosocial risk factor was substance abuse in 1941 (12.6%) recipients. Patients with psychosocial risk factors were significantly younger at LVAD implant, less likely to be white, and less likely to be female compared to those without psychosocial risk, p <0.001 for all. Patients with psychosocial risk were significantly more likely to receive an LVAD as destination therapy, p <0.001. In adjusted models, patients with psychosocial risk were at increased hazards for device-related infection, gastrointestinal bleeding, pump thrombosis, and readmission and reduced hazards for cardiac transplantation (p<0.05 for all). There was no statistically significant difference in survival on pump support or stroke. CONCLUSIONS: Psychosocial risk is an important component of patient selection for advanced heart failure therapies. Addressing these specific components may help improve access to advanced therapies and post-LVAD outcomes.